Effect of plyometric training on jumping performance and agility in adolescent badminton players - Tarik Ozmen; Mert Aydogmus (Selcuk University, 2017)
Badminton is one of the most popular racquet sports in the world. The agility and vertical jump are important motor skills to hit a shuttlecock in badminton game. The purpose of this study was to investigate effect of plyometric training on vertical jump and agility in adolescent badminton players. Twenty adolescent (age, 12.5 ± 0.2 years) badminton players were randomly divided into two groups as plyometric group (PG) and control group (CG). All participants were tested to assess agility and vertical jump before (pre-test) and after 6-weeks training period (post-test). Agility performance was assessed with Illinois Agility Test. Vertical jump height was measured with squat jump test using a contact mat. The PG performed plyometric training twice a week, for 6 weeks. There was a significant difference between pre and post-test for squat jump test in both PG (26%) (p = 0.00) and CG (10%) (p = 0.016). However, squat jump height significantly increased in PG compared with CG (p = 0.024). The agility significantly improved in PG (6%) (p = 0.01), but not CG (2%) (p = 0.294). Our results show that a six week plyometric training improved agility and vertical jump in adolescent badminton players. Badminton game requires fast changes in direction, vertical jumps, forward lunges around the court. Badminton coaches should take place plyometric exercises in training program.